Low serum magnesium and 1‐year mortality in alcohol withdrawal syndrome. (1st July 2019) - Maguire, Donogh; Ross, David P.; Talwar, Dinesh; Forrest, Ewan; Naz Abbasi, Hina; Leach, John‐Paul; Woods, Marylynne; Zhu, Luke Y.; Dickson, Scott; Kwok, Tong; Waterson, Isla; Benson, George; et al.
Abstract: Background: In 2014, the WHO reported that 6% of all deaths were attributable to excess alcohol consumption. The aim of the present study was to examine the relationship between serum magnesium concentrations and mortality in patients with alcohol withdrawal syndrome (AWS). Materials and methods: A retrospective review of 700 patients with documented evidence of previous AWS indicating a requirement for benzodiazepine prophylaxis or evidence of alcohol withdrawal syndrome between November 2014 and March 2015. Results: Of 380 patients included in the sample analysis, 64 (17%) were dead at 1 year following the time of treatment for AWS. The majority of patients had been prescribed thiamine (77%) and a proton pump inhibitor (66%). In contrast, the majority of patients had low circulating magnesium concentrations (<0.75 mmol/L) (64%) and had not been prescribed magnesium (90%). The median age of death at one year was 55 years ( P  = 0.002). On univariate analysis, age ( P  < 0.05), GMAWS ( P  < 0.05), BDZ ( P  < 0.05), bilirubin ( P  < 0.001), alkaline phosphatase ( P  < 0.001), albumin ( P  < 0.001), CRP ( P  < 0.05), AST:ALT ratio >2 ( P  < 0.001), sodium ( P  < 0.05), magnesium ( P  < 0.001), platelets ( P  < 0.05) and the use of proton pump inhibitor medication ( P  < 0.001) were associated with death at 1 year. On multivariate binary logistic regression analysis, age > 50 years (OR 3.37, 95% CI 1.52‐7.48, P  < 0.01), AST:ALT ratio >2 (OR 3.10, 95% CI 1.38‐6.94, P  < 0.01) and magnesium < 0.75 mmol/L (OR 4.11, 95% CI 1.3‐12.8, P  < 0.05) remained independently associated with death at 1 year. Conclusion: Overall, 1‐year mortality was significantly higher among those patients who were magnesium deficient (<0.75 mmol/L) when compared to those who were replete (≥0.75 mmol/L; P  < 0.001).